2018
DOI: 10.1093/rap/rky041
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the development of systemic sclerosis: a systematic review of the literature

Abstract: Objectives Although numerous studies have investigated the roles of various genetic, epigenetic and environmental factors that may impact its aetiology, SSc is still regarded as an idiopathic disease. Given that there is significant heterogeneity in what has been proposed to influence the development of SSc, this systematic review was conducted to assess the impacts of different factors on the aetiology of scleroderma. Methods The search was performed in the PubMed, CIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 52 publications
0
18
0
1
Order By: Relevance
“…The etiology of SSc is multifactorial. The various factors that are involved in the etiology and associations of SSc are shown in Table 1 [7][8][9][10][11][12][13][14][15][16]. However, there are familial aggregates of SSc [13].…”
Section: Etiology and Associations Of Sscmentioning
confidence: 99%
See 1 more Smart Citation
“…The etiology of SSc is multifactorial. The various factors that are involved in the etiology and associations of SSc are shown in Table 1 [7][8][9][10][11][12][13][14][15][16]. However, there are familial aggregates of SSc [13].…”
Section: Etiology and Associations Of Sscmentioning
confidence: 99%
“…In a systematic review and a meta-analysis that included 34 published studies, the following results were obtained [8]: 1. The confirmed risk factors included: female gender, age between 45 and 64 years, positive family history, and exposure to silica 2.…”
Section: Etiology and Associations Of Sscmentioning
confidence: 99%
“…CREST syndrome -the name comes from the first letter of the main symptoms of the disease: Calcinosis, Raynaud's Phenomenon, Esophageal dysfunction, Sclerodactyly, Telangiectasia. 8 years of age may point to hormonal predisposition, and low birthweight is considered as an independent risk factor of SSc [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies show that the disease is more common in subjects with a certain genetic predisposition, such as the presence of the HLA-DRB1 *10 antigen [ 3 ], or after exposure to specific environmental factors (various viruses, toxins, drugs). The more frequent occurrence in girls after 8 years of age may point to hormonal predisposition, and low birthweight is considered as an independent risk factor of SSc [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a 2018 review, Abbot et al concluded that exposure to silicates alone is an important risk factor. Various authors express divergent views concerning exposure to organic solvents ( 15 ). In another review, Walecka et al highlighted the role of silicates in the etiology of SSc, but also of multiple organic solvents such as ketones, aromatic and aliphatic hydrocarbons, white spirit solvent for oil-based paints, smoke from welding; underlining the need for protective measures for workers with such occupational exposure.…”
Section: Introductionmentioning
confidence: 99%